Pelatihan Manajemen Keorganisasian untuk Menguatkan Stabilitas Kelembagaan di Masa Pandemi di TPQ Hidayatul Mubtadi’in Dusun Sukosari Sukorejo Udanawu Blitar - M. Tajil Arifin; Haryadi (LP3M IAIFA Kediri, 2021)
During a pandemic like this, of course, every educational institution will experience disturbances in its stability, for this reason, training is needed for the younger generation who will later take control of the management of the educational institution so that they will be ready and able to maintain the stability of educational institutions with various uncertain conditions such as recently. The organizational management training held at TPQ Hidayatul Mubtadi'in aims to provide new experience and knowledge for students about organization and how to apply it in good and right educational institutions. Meanwhile, for the implementation of this training, several methods are needed that must be used to make this training activity successful and of course get the desired results, for example, there must be careful planning, good communication and also the material delivered must be in accordance with the environmental conditions that exist around the institution. where this training is carried out. This training can be said to be successful because there are significant social changes in the students who take part in the training activities, they have a more responsible attitude towards the tasks they get different from before the training.